A ten year analysis of dissertation bibliographies from the Department of Spanish and Portuguese at Rutgers University. Issue 3 (1st July 2014) - Gasparotto, Melissa
Abstract : Purpose: – The purpose of this paper is to analyze the bibliography citations from dissertations submitted to the Department of Spanish and Portuguese at Rutgers University from the ten-year period of 2003-2012. The objective of the analysis is to aid in collection development decisions, facilitate outreach to graduate students in the department and to understand possible changes in disciplinary methodologies and research needs in the field over the last decade. Design/methodology/approach: – Descriptive research design was used for the study. Bibliography citation data were extracted from all dissertations submitted to the Department of Spanish and Portuguese from the period 2003-2012. Statistical analysis was performed on the collected citation data, and conclusions were drawn from the results. Findings: – The study demonstrates that, despite the oft-mentioned "decline of the monograph", the monograph remains very heavily used by PhD students in Spanish and Portuguese at Rutgers University, and that monographs continue to be cited at significantly higher rates and for longer periods than journal articles. This holds true for the humanities dissertations in Spanish literature as well as social science dissertations in Spanish linguistics. The study further finds that open access journals in Spanish literature are cited more frequently than closed access journals. Practical implications: – The findings suggest that it is more user-responsive to allocate retrospective collections funds for filling in monographic gaps than journal coverage gaps, as journal articles are cited less frequently and for shorter periods, while monographs are cited more frequently and for slightly longer periods after they are published. The findings also suggest that current monographic expenditures be maintained or augmented to continue serving current and future graduate student research needs in Spanish and Portuguese. Further, the large number of monograph chapters cited suggests that book chapter document delivery services could be an important addition to a library's suite of services if it is not already provided. Originality/value: – This paper is the first analysis of Spanish and Portuguese dissertations conducted at Rutgers University and provides important contextual information for meeting the research needs of graduate students in the department through collection development and related services. Other research has documented that dissertation citation patterns are at least partially predictive of faculty citation patterns, making the findings of this study applicable to serving faculty research and collections needs in the department, as well. The findings are relevant to collection development, access services and librarian-department liaison relationships.